The impact of organizational rigidity on limiting the development of proactive behavior in financial institutions: An exploratory study of the opinions of a sample of employees in government banks in the Zakho Independent Administration - ئامێدي, د. ﮔرين مصطفى خالد ئامێدي; Mohamed, Basma Ahmed Mohamed (Sulaimani Journal for Humanities, 2026)
This research aims to evaluate the impact of organizational rigidity on limiting the development of proactive behavior among employees in governmental financial institutions, in light of the accelerating shift toward digitalization and technological advancement in the financial sector. The study adopted the descriptive–analytical approach to handle both theoretical and field data. The research population included employees working in government banks under the Zakho Independent Administration, with a final sample size of (99) employees. Data were collected through a questionnaire and statistically analyzed using (SPSS V.27 and AMOS V.25), employing a set of statistical indicators that formed the basis for presenting, discussing, and interpreting the field analysis results. The findings revealed a significant negative correlation between organizational rigidity and proactive behavior, indicating that higher levels of organizational rigidity weaken employees’ ability to take initiative and innovate within the work environment—especially amid rapid changes. The results also showed that organizational rigidity and its dimensions have a significant and negative effect on developing proactive behavior, which in turn limits the ability of financial institutions, including the studied government banks, to keep up with digital transformations and achieve competitive sustainability. Based on these findings, the study presented several practical recommendations for the surveyed government banks, most notably the need to empower leaders to support change and encourage developmental initiatives so they can act as the first line of defense against organizational rigidity while inspiring employees to generate creative ideas that enhance banking performance and operational efficiency. The study further emphasizes the importance of promoting a culture of teamwork and administrative empowerment, enabling government banks in Zakho Independent Administration to overcome the negative effects of organizational rigidity and transform proactive behavior into a key driver for performance sustainability, service quality improvement, and adaptation to modern technological and digital transformations that increasingly define the framework of contemporary banking operations—helping maintain their competitive advantage both locally and internationally. Surveyed government banks, most notably the need to empower leaders to support change and encourage developmental initiatives so they can act as the first line of defense against organizational rigidity while inspiring employees to generate creative ideas that enhance banking performance and operational efficiency. The study further emphasizes the importance of promoting a culture of teamwork and administrative empowerment, enabling government banks in Zakho Independent Administration to overcome the negative effects of organizational rigidity and transform proactive behavior into a key driver for performance sustainability, service quality improvement, and adaptation to modern technological and digital transformations that increasingly define the framework of contemporary banking operations—helping maintain their competitive advantage both locally and internationally.
Keywords: Stagnation in change leadership; stagnation in organizational culture; stagnation in job requirements; stagnation in motivation; proactive behavior; government banks in the independent administration of Zakho